Synthetic glycopolypeptides: synthesis and self-assembly of poly(γ-benzyl-l-glutamate)-glycosylated dendron hybrids. Issue 45 (30th September 2015) - Peyret, Ariane; Trant, John F.; Bonduelle, Colin V.; Ferji, Khalid; Jain, Namrata; Lecommandoux, Sebastien; Gillies, Elizabeth R.
Abstract : Polyester dendrons with peripheral α-galactose moieties were synthesized and coupled to poly(γ-benzyl-l -glutamate) to afford amphiphilic linear-dendron hybrid glycopolypeptides that self-assembled in water. Abstract : Nano-assemblies prepared from glycosylated macromolecules are promising systems for modulating or mimicking the interactions between natural carbohydrates and their receptors. In the current work, polyester dendrons bearing focal point alkynes and peripheral C -linked α-galactose moieties were synthesized and coupled to helical poly(γ-benzyl-l -glutamate) (PBLG) to afford synthetic linear-dendritic glycopolypeptides. Both the dendrimer generation and the length of the PBLG were varied to provide a small library of amphiphiles with hydrophilic mass fractions ranging from 0.07 to 0.54. The self-assembly of the copolymers in water using a solvent exchange method was optimized and studied in detail. While the linear-dendritic copolymers composed of lower generation dendrons tended to aggregate, a copolymer composed of a 4 th generation galactose-functionalized dendron and PBLG with a degree of polymerization of 28 formed micellar nano-assemblies whose size could be tuned by varying the self-assembly process. Overall, this study provides new insights into the effects of polymer architecture on self-assembly properties, while at the same time introducing a new platform for the preparation of bioactive nanoparticles.